Pertanggungjawaban Terhadap Perbuatan Melawan Hukum Dalam Pengadaan Ternak Sapi - Meria, Fatma; Holijah, Holijah; Tanzil, Mulyadi; Mahfuz, Abdul Latif (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The purpose of the paper is to understand the legal responsibility faced by individuals or entities in the event of unlawful acts in the procurement of cattle. In the cattle procurement industry, there are often practices that are not in accordance with the law, such as falsification of documents, improper feeding, and fraud in transactions. This research method used is a normative juridical approach, this study examines various regulations, regulations, and legal cases relevant to illegal acts in the procurement of cattle. The results of this study show that there is a strict legal framework governing the responsibility of individuals or entities that commit unlawful acts in the procurement of cattle. Business actors are expected to understand and comply with applicable regulations to avoid sanctions and ensure the sustainability of their business in the cattle procurement industry.